PENINGKATAN KUALITAS DAN KUANTITAS PRODUKSI BATIK KHAS PASURUAN PADA PENGRAJIN BATIK DI KECAMATAN BANGIL KABUPATENPASURUAN - Sujito, '; Yunus, Mahmud; Trisno Sami, Sri Esti (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
The development of batik business in Bangil sub-district of Pasuruan Regency is still very promising, due to the increasing demand of batik products and its derivatives, there are many batik craftsmen, the existence of local government policies that encourage the growth of batik business, and the opportunity to utilize information technology to expand the marketing area . But these factors can not be optimized, because the process of producing batik takes a long time, the amount of batik equipment is very limited, marketing is still limited due to the number of small and conventional production; and have not applied good business management for business development. Based on this, the purpose of this activity is to help improve the status of business partners from household business to micro business. The solutions include: (1) providing equipment and production process improvement training such as (a) the use of batik motif, wok and table cap to accelerate the process of printing motifs to fabrics; and (b) use of dyed bags, lorod stoves and lantern pans for staining processes; (2) utilization of online media for marketing system development; (3) business management training includes: (a) improvement of raw material procurement planning system; (b) improvement of production system and quality control, and (c) improvement of accounting system. Activities undertaken can improve the quality and quantity of batik production of partners.